Software regla y compás como recurso didáctico para el aprendizaje significativo del bloque de geometría y medida de matemática en noveno año - Jiménez Jiménez, Jhoanna Marisol (2023)
The present research focused on identifying how the educacional software: Compass and Ruler improves the significant learning of the Geometry and Measurement block in the ninth year of General Basic Education. The study followed a descriptive qualitative approach, it was based on a documentary research, a bibliographic review of primary and secondary sources which was conducted to identify theoretical conceptualizations of previous empirical works related to the C.a.R. software applied in educational contexts. The collection of information consisted of using a search logbook and content cards. The results obtained show that “compass and ruler” is an interactive and dynamic software, it facilitates the visualization, transformation, interaction and analysis of different geometric constructions, improves the student’s skills through practice and helps of development of meaningful learning, so a didactic guide is proposed to implement this software in the teaching learning-process of geometry and measurement. Key words: software, educational technology, geometry, teaching, learning.